Is life cycle assessment enough to address unintended side effects from Circular Economy initiatives? - Niero, Monia; Jensen, Charlotte L.; Fratini, Chiara Farné; Dorland, Jens; Jørgensen, Michael S.; Georg, Susse (Journal of industrial ecology, 2021)
Despite the spread of policy and business initiatives aiming at transitioning to a Circular Economy (CE), the concept is criticized in the scientific literature for its lack of emphasis on social contexts. Implementing CE initiatives to production systems can indeed lead to “unintended side effects,” that is, both rebound effects and other indirect shifts in consumption patterns. In this forum article we address the question: “How to make the unintended side effects of implementing CE initiatives knowable and actionable?” We argue that the ability of life cycle assessment (LCA) to address unintended side effects from CE initiatives is limited, as LCA can model how different product systems interact with each other, but does not attend to the socio‐technical dynamics taking place within and across different life cycle phases. To extend the potential of LCA in supporting decision‐making, our suggestion is to complement LCA with other types of analytical approaches, such as Practice Theory (PT) and Actor‐Network Theory (ANT), which can improve our understanding of the unintended side effects of CE initiatives. These theories consider societal dynamics as socio‐technical and focus on the processes and practices through which production and consumption dynamics change. Thus, they can provide analyses of whether and how CE initiatives are capable of realizing novel relations within/among socio‐technical systems. Ultimately, they can provide explanations on why things end up the way they do, thus supporting LCA in the investigation of more "real" rather than ideal scenarios.